Ascorbic acid promoted magnetite Fenton degradation of alachlor: Mechanistic insights and kinetic modeling - Sun, Hongwei; Xie, Guihong; He, Di; Zhang, Lizhi (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Ascorbic acid greatly enhanced Fenton performance of Fe3O4/H2O2 system.•A kinetic model was developed to quantitatively describe Fe3O4/AA/H2O2 system.•Individual contributions of surface and homogeneous Fenton reaction were simulated.•Surface Fenton reaction mainly contributed to the overall alachlor degradation by more than 62.6%. In this study we constructed a heterogeneous Fenton system with ascorbic acid (AA), magnetite (Fe3O4) and H2O2 for the alachlor degradation, aiming to clarify the heterogeneous Fenton mechanism. The addition of AA could significantly accelerate the Fenton reaction by promoting the surface Fe(III)/Fe(II) redox cycle (iron cycle) of Fe3O4. A kinetic model was successfully developed to quantitatively describe the complicated reactions in the Fe3O4/AA/H2O2 system. We thus employed this model to identify the individual contributions of surface and homogeneous Fenton reactions to the overall alachlor degradation in the Fe3O4/AA/H2O2 system, and found the surface Fenton reaction was mainly responsible for the alachlor degradation with more than 62.6% of contribution. This work offers a new strategy to improve the heterogeneous Fenton activity via promoting surface Fenton reaction, and sheds light on the possibility to quantitatively describe and predict the heterogeneous Fenton processes with first principle kinetic models.